Profils quantiques des raies de résonance des ions Mg+ perturbé par des collisions avec He - KECHRADI Lamisse (My University, 2025)
Abstract: We treat in this work the phenomenon of pressure broadening in the wings of the D1 (3s2S1/2 − 3p2P1/2) and D2 (3s2S1/2 − 3p2P3/2) lines of the Mg+ magnesium ion perturbed by ground state He Helium atoms. We first calculate the potential curves and transition dipole moments (TDM) by an (ab-initio) method, including RCCSD (T) and SA-CASSCF/MRCI, with the incorporation of Davidson and BSSE correction and the spin orbit effect. Then, we evaluate this PECs and TDMs by determining some spectroscopic parameters, the vibrational energy levels and the lifetimes of the vibrational levels of the excited states A2Π1/2 and A2Π3/2. Finally, we determine the absorption spectra in a range of wavelengths from 200 to 450nm, and at temperature of 4000, 6000, 8000, 10000, and 12000K. A satellite peak is observed in the blue wing at around 235nm, which is associated to the B2Σ+1/2 ←− X2Σ+1/2 transitions. The results found agree well with previous work. Keywords:Pressure broadening, Potential energy curves, Transition dipole moment, Spectroscopic parameters
Résumé: Nous traitons dans ce travail le phénomène d’élargissement de pression dans les ailes des raies D1 (3s2S1/2 − 3p2P1/2) et D2(3s2S1/2 − 3p2P3/2) des ions Mg+ perturbés par des collisions avec les atomes He d’Helium. Premièrement, nous calculons les courbes d’énergie potentielle (PECs) et les moments dipolaires de transition (TDMs) par les méthodes ab-initio à savoir RCCSD (T), SA-CASSCF/MRCI en tenant compte de la correction de Davidson, l’erreur de superposition de base et l’effet spin orbite. Après, nous évaluons ces PECs et TDMs par la détermination de quelque paramètres spectroscopiques, des niveaux l’énergie vibrationnelle, et de durés de vies des niveaux vibrationnelle des etats excités A2Π1/2, A2Π3/2. Finalement, nous déterminons le spectre d’absorption dans une gamme de longueur d’onde allant de 200 à 450nm, et à des temperatures de 4000,6000,8000,10000, et 12000K. Un satellite est observé dans l’aile bleu àenviron 235nm, il est associe à la transition B2Σ+1/2 ←− X2Σ+1/2 de type libre-libre. Les résultats obtenus concordent bien avec les travaux précédents. Mots clés:Elargissement de pression, courbes d’énergie potentielle, moment dipolaire de transition, paramètres spectroscopiques
Keywords: Keywords:Pressure broadening; Potential energy curves; Transition dipole moment; Spectroscopic parameters; الكلمات المفتاحية التوسع الضغطي - منحنيات الطاقة الكامنة - عزوم الاقطاب الانتقالية - المعاملات الطيفية.; Mots clés:Elargissement de pression; courbes d’énergie potentielle; moment dipolaire de transition; paramètres spectroscopiques